Structural Phase Diagram of LaO1−xFxBiSSe: Suppression of the Structural Phase Transition by Partial F Substitutions - Kazuhisa Hoshi; Shunsuke Sakuragi; Takeshi Yajima; Yosuke Goto; Akira Miura; Chikako Moriyoshi; Yoshihiro Kuroiwa; Yoshikazu Mizuguchi (Condensed Matter, 2020)
Recently, the anomalous two-fold-symmetric in-plane anisotropy of superconducting states has been observed in a layered superconductor system, LaO1−xFxBiSSe (x = 0.1 and 0.5), with a tetragonal (four-fold symmetric) in-plane structure. To understand the origin of the phenomena observed in LaO1−xFxBiSSe, clarification of the low-temperature structural phase diagram is needed. In this study, we have investigated the low-temperature crystal structure of LaO1−xFxBiSSe (x = 0, 0.01, 0.02, 0.03, and 0.5). From synchrotron X-ray diffraction experiments, a structural transition from tetragonal to monoclinic was observed for x = 0 and 0.01 at 340 and 240 K, respectively. For x = 0.03, a structural transition and broadening of the diffraction peak were not observed down to 100 K. These facts suggest that the structural transition could be suppressed by 3% F substitution in LaO1−xFxBiSSe. Furthermore, the crystal structure for x = 0.5 at 4 K was examined by low-temperature laboratory X-ray diffraction, which confirmed that the tetragonal structure is maintained at 4 K for x = 0.5. Our structural investigation suggests that the two-fold-symmetric in-plane anisotropy of superconducting states observed in LaO1−xFxBiSSe was not originated from structural symmetry lowering in its average structure. To evaluate the possibility of the local structural modification like nanoscale puddles in the average tetragonal structure, further experiments are desired.